Peptide‐Perovskite Based Bio‐Inspired Materials for Optoelectronics Applications - Samrana Kazim; M. P. U. Haris; Shahzada Ahmad (Advanced Science)
Abstract The growing demand for environmentally friendly semiconductors that can be tailored and developed easily is compelling researchers and technologists to design inherently bio‐compatible, self‐assembling nanostructures with tunable semiconducting characteristics. Peptide‐based bioinspired materials exhibit a variety of supramolecular morphologies and have the potential to function as organic semiconductors. Such biologically or naturally derived peptides with intrinsic semiconducting characteristics create new opportunities for sustainable biomolecule‐based optoelectronics devices. Affably, halide perovskite nanocrystals are emerging as potentially attractive nano‐electronic analogs, in this vein creating synergies and probing peptide‐perovskite‐based bio‐electronics are of paramount interest. The physical properties and inherent aromatic short‐peptide assemblies that can stabilize, and passivate the defects at surfaces assist in improving the charge transport in halide perovskite devices. This review sheds light on how these peptide‐perovskite nano‐assemblies can be developed for optical sensing, optoelectronics, and imaging for biomedical and healthcare applications. The charge transfer mechanism in peptides along with as an outlook the electron transfer mechanism between perovskite and short peptide chains, which is paramount to facilitate their entry into molecular electronics is discussed. Future aspects, prevailing challenges, and research directions in the field of perovskite‐peptides are also presented